Angles from a socio-cultural perspective - Saida ZIZAH; Sabiha BOUKHADOUNI (Social Sciences Journal, 1970)
In light of the social and political transformations taking place in Algerian society, all religious and social institutions were subjected to a change in functions and roles, but the angles continued to provide their functions, especially in recent times, where they regained their activity and their social, cultural and religious status, as an institution with It is a religious and social character that has the right to exercise all its functions, as it is a place where all segments of society meet, regardless of their educational, social, and economic levels. The angles play effective social roles, especially at the present time, in addition to their role in social reform, resolving conflicts, and working to find solutions to social problems. It is "all individuals within the corners are equal where all differences dissolve."